From formative design to service-ready therapeutic: A pragmatic approach to designing digital mental health interventions across domains - Jonah Meyerhoff; Rachel Kornfield; Emily G. Lattie; Ashley A. Knapp; Kaylee P. Kruzan; Maia Jacobs; Caitlin A. Stamatis; Bayley J. Taple; Miranda L. Beltzer; Andrew B.L. Berry; Madhu Reddy; David C. Mohr; et al. (Internet Interventions, 2023)
As digital mental health interventions (DMHIs) proliferate, there is a growing need to understand the complexities of moving these tools from concept and design to service-ready products. We highlight five case studies from a center that specializes in the design and evaluation of digital mental health interventions to illustrate pragmatic approaches to the development of digital mental health interventions, and to make transparent some of the key decision points researchers encounter along the design-to-product pipeline. Case studies cover different key points in the design process and focus on partnership building, understanding the problem or opportunity, prototyping the product or service, and testing the product or service. We illustrate lessons learned and offer a series of questions researchers can use to navigate key decision points in the digital mental health intervention (DMHI) development process.